Cardiolipin externalization mediates prion protein (PrP) peptide 106–126-associated mitophagy and mitochondrial dysfunction - Yang, Dongming; Li, Jie; Li, Zhiping; Zhao, Mengyang; Wang, Dongdong; Sun, Zhixin; Wen, Pei; Gou, Fengting; Dai, Yuexin; Ji, Yilan; Li, Wen; Zhao, Deming; et al. (Frontiers in Molecular Neuroscience, 2023)
Proper mitochondrial performance is imperative for the maintenance of normal neuronal function to prevent the development of neurodegenerative diseases. Persistent accumulation of damaged mitochondria plays a role in prion disease pathogenesis, which involves a chain of events that culminate in the generation of reactive oxygen species and neuronal death. Our previous studies have demonstrated that PINK1/Parkin-mediated mitophagy induced by PrP106−126 is defective and leads to an accumulation of damaged mitochondria after PrP106−126 treatment. Externalized cardiolipin (CL), a mitochondria-specific phospholipid, has been reported to play a role in mitophagy by directly interacting with LC3II at the outer mitochondrial membrane. The involvement of CL externalization in PrP106−126-induced mitophagy and its significance in other physiological processes of N2a cells treated with PrP106−126 remain unknown. We demonstrate that the PrP106−126 peptide caused a temporal course of mitophagy in N2a cells, which gradually increased and subsequently decreased. A similar trend in CL externalization to the mitochondrial surface was seen, resulting in a gradual decrease in CL content at the cellular level. Inhibition of CL externalization by knockdown of CL synthase, responsible for de novo synthesis of CL, or phospholipid scramblase-3 and NDPK-D, responsible for CL translocation to the mitochondrial surface, significantly decreased PrP106−126-induced mitophagy in N2a cells. Meanwhile, the inhibition of CL redistribution significantly decreased PINK1 and DRP1 recruitment in PrP106−126 treatment but had no significant decrease in Parkin recruitment. Furthermore, the inhibition of CL externalization resulted in impaired oxidative phosphorylation and severe oxidative stress, which led to mitochondrial dysfunction. Our results indicate that CL externalization induced by PrP106−126 on N2a cells plays a positive role in the initiation of mitophagy, leading to the stabilization of mitochondrial function.